State of knowledge on early warning tools for cyanobacteria detection. (December 2021) - Almuhtaram, Husein; Kibuye, Faith A.; Ajjampur, Suraj; Glover, Caitlin M.; Hofmann, Ron; Gaget, Virginie; Owen, Christine; Wert, Eric C.; Zamyadi, Arash
Highlights: Cyanobacteria adversely impact recreational and drinking water sources. Monitoring tools are used to detect the onset of cyanobacteria blooms. Each tool has its own advantages, limitations, and opportunities for application. Multi-tool monitoring systems are necessary to fully capture cyanobacteria risk. Abstract: The potential for cyanobacterial blooms to impact recreational and drinking water source quality is a growing concern. Numerous monitoring tools have been developed that can alert stakeholders to the onset of cyanobacterial blooms to initiate mitigation efforts for waters used for recreation or drinking water supply. Early warning monitoring systems need to consider multiple aspects of a cyanobacterial bloom: whether a bloom is occurring in the source water, whether it might be transported to drinking water intakes, whether toxin or taste and odor compound producers are present and what proportion of the cells in a bloom they comprise, and whether cells are entering a utility at concentrations above threshold levels. No single monitoring tool can provide all this information, so multi-barrier approaches are needed. Reviews of monitoring tools and their variations are available, but they are generally limited to one type of tool. Instead, a review and comparison of all the available tools is needed to inform stakeholders of them and their relative advantages and limitations. Therefore, this review covers conventional tools including microscopic enumeration, pigment extraction, qPCR, probes, and remote sensing as well as emerging techniques including next-generation sequencing, photonic systems, biosensors, drones, and applications of machine learning and discusses them primarily from a practical and operational standpoint. Moreover, a three-tier framework is proposed for designing comprehensive early warning systems that groups monitoring tools by their analytical targets: biological activity or algal biomass, cyanobacteria or cyanobacteria-related genes, and cyanobacterial metabolites. First tier tools are generally simple and inexpensive to use, including turbidity, optical density, visual inspection, drones, chlorophyll a, and adenosine triphosphate. Changes in water quality conditions detected using a first tier tool triggers the use of a second tier tools for identification and quantification of cyanobacteria by microscopy, phycocyanin, biosensors, hyperspectral remote sensing, or next-generation sequencing. If potentially harmful concentrations of cyanobacteria are confirmed, third tier tools are deployed for quantifying concentrations of cyanotoxins and taste and odor compounds or the genes that encode for them using enzyme-linked immunosorbent assays, mass spectrometry, qPCR, or other analytical methods. This framework is designed to minimize the time and cost associated with cyanobacteria monitoring without compromising the ability of stakeholders to detect the onset of a bloom.